1995
DOI: 10.1007/bf00546881
|View full text |Cite
|
Sign up to set email alerts
|

Properties and erosional response of soils in a degraded ecosystem in Crete (Greece)

Abstract: To study desertification processes relating to soil erosion, a climatological and altitudinal gradient from south to north was selected in Crete (Greece) and four locations were selected along the gradient. At the locations precipitation ranged from 1400 mm/year at the highest location to 400 mm/year at the lowest. All locations are affected by the actual land use: intensive grazing, small controlled fires, and abandoned agricultural terraces. Representative soil profiles were described in the field and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 5 publications
2
8
1
1
Order By: Relevance
“…Another ratio has been calculated between the source runoff area (the sum of the areas with embedded RF, crusts and rock outcrops) versus sink runoff area (the sum of the areas with vegetation and areas without embedded RF). In this case, the climatic gradient is even less fulfi lled, and AB has higher values of source areas, followed by CO, with an indicative result for the values of soil degradation because, despite having the greatest rainfall, the soil conditions and vegetation cover, depleted as a result of grazing, have given rise to the greatest number of surface components that are a priori favourable to the production of runoff and therefore water erosion; similar results were obtained by Boix et al (1995) on calcareous hillslopes. Furthermore, CO is characterized by a large area of rock outcrops, localized in the lower zone of the hillside due to the steep slope (>50%) and the compact situation of the gully.…”
Section: Soil Surface Componentssupporting
confidence: 83%
See 1 more Smart Citation
“…Another ratio has been calculated between the source runoff area (the sum of the areas with embedded RF, crusts and rock outcrops) versus sink runoff area (the sum of the areas with vegetation and areas without embedded RF). In this case, the climatic gradient is even less fulfi lled, and AB has higher values of source areas, followed by CO, with an indicative result for the values of soil degradation because, despite having the greatest rainfall, the soil conditions and vegetation cover, depleted as a result of grazing, have given rise to the greatest number of surface components that are a priori favourable to the production of runoff and therefore water erosion; similar results were obtained by Boix et al (1995) on calcareous hillslopes. Furthermore, CO is characterized by a large area of rock outcrops, localized in the lower zone of the hillside due to the steep slope (>50%) and the compact situation of the gully.…”
Section: Soil Surface Componentssupporting
confidence: 83%
“…Extensive study has been carried out into soil erosion by water in the Mediterranean mountains, mainly in calcareous substratum where a combination of both the climatic gradient approach and rainfall simulation on surface components on the hillslopes were used to establish a hydrological response Boix et al, 1995;Cerdà et al, 1996;Bergkamp et al, 1999;Calvo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the Southern Piedmont, Franzluebbers et al (2000Franzluebbers et al ( , 2008 reported that cattle grazing did not adversely affect aggregate size and stability. In contrast, other studies indicated that grazing reduced stability of microaggregates (Boix et al, 1995) and macroaggregates (Proffitt et al, 1995). In the present study, the effect of grazing treatment on soil aggregation was somewhat mixed.…”
Section: Discussioncontrasting
confidence: 75%
“…This is the case in the majority of published descriptions of rainfall simulation experiments, where all that is usually described is the mean rainfall intensity applied to the soil surface for a specified length of time (e.g. Boix et al, 1995;Bergkamp et al, 1996;Bergkamp, 1998;Cerda Á 1998a;Eldridge, 1998;Chappell et al, 1999). Occasionally the mean kinetic energy and drop size of the simulated rainfall are also described (Morgan et al, 1997;Cerda Á 1998b).…”
Section: Introductionmentioning
confidence: 95%